2021
DOI: 10.1007/s11764-020-00984-7
|View full text |Cite
|
Sign up to set email alerts
|

Working cancer survivors’ physical and mental characteristics compared to cancer-free workers in Japan: a nationwide general population-based study

Abstract: Purpose This study compared working cancer survivors’ self-rated health status (SRHS), physical functional capacity, depressive symptoms, and happiness to those of cancer-free workers. Methods A nationwide general population-based cross-sectional study on a sample of Japanese was conducted. Prevalence of deteriorated SRHS, restricted physical functional capacity, depressive symptoms, and perceived happiness were compared between working cancer survivors an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Kohout et al explained that it is appropriate to lower or raise the used cutoff point to guard against false positives or negatives as it suits the study’s population. 38 We tested the associations using different cutoff points indicating depression; ≥7 as Kohout et al, 38 ≥8 as Ota et al, 30 ≥9 as Torres, 37 and ≥10 points of the CES-D score, and the associations did not change materially. Last, despite the explicit explanation given to the Egyptian participants regarding the meaning of the ikigai question, a gap might still be present between the Japanese and Egyptian understanding of the ikigai concept.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kohout et al explained that it is appropriate to lower or raise the used cutoff point to guard against false positives or negatives as it suits the study’s population. 38 We tested the associations using different cutoff points indicating depression; ≥7 as Kohout et al, 38 ≥8 as Ota et al, 30 ≥9 as Torres, 37 and ≥10 points of the CES-D score, and the associations did not change materially. Last, despite the explicit explanation given to the Egyptian participants regarding the meaning of the ikigai question, a gap might still be present between the Japanese and Egyptian understanding of the ikigai concept.…”
Section: Discussionmentioning
confidence: 99%
“…Each item in the scale was rated on a four-Likert score (0 = rarely to 3 = always). According to a previous study in Japan, 30 a score ≥8 indicated depression.…”
Section: Methodsmentioning
confidence: 99%
“…In an attempt to quantify the magnitude of these challenges at a national level, the prevalence of current smokers and drinkers among cancer survivors has been estimated and compared with the rates among persons without cancer histories in studies from several countries which analyzed survey data from nationally representative samples. [6][7][8][9][10][11][12][13][14][15][16][17] In Japan, studies have reported the crude prevalence of smokers and drinkers among cancer survivors and subjects with no history of cancer as part of cross-sectional 18 or prospective cohort studies. 19 However, no study in Japan has focused specifically on a comparison of the age-adjusted prevalence of current smokers and drinkers between cancer survivors and subjects with no history of cancer, either using a nationally representative sample or a nonrepresentative sample.…”
Section: Introductionmentioning
confidence: 99%
“…than noncancer workers. 5 Helping cancer survivors who return to work after treatment such as operation, chemotherapy, and radiation should be a priority to protect these individuals' right to work and preserve the overall workforce. 6 The long-term medical and psychological effects of not only cancer but also other chronic illnesses and their treatments may also include impairments that reduce physical and emotional capacity for employment.…”
mentioning
confidence: 99%
“…A significant percentage of people with chronic illnesses experience physical, mental, and social problems (eg, anxiety, cognitive deficits, fatigue, pain, and depression), which may be prolonged 2–4 . A previous study showed that working cancer survivors who undergo cancer treatment had a poorer self-rated health status and more limited physical functional capacity than noncancer workers 5 . Helping cancer survivors who return to work after treatment such as operation, chemotherapy, and radiation should be a priority to protect these individuals’ right to work and preserve the overall workforce 6 .…”
mentioning
confidence: 99%